FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI UPPD SAMSAT BATULICIN - Damar Bayu Saputra; Fatkhan; Muhammad; Efrianto, Eko; Risanta, Muhammad; Yanti, Nofarina Maulida (Jurnal Ilmu Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine which variables affect taxpayer compliance at UPPD Samsat Batulicin. The sample in this study is the people who carry out management at UPPD Samsat Batulicin as many as 384 people. The method used in this study is quantitative data analysis techniques which are processed using SPSS Version 26 app The results of this study are where knowledge, awareness, satisfaction, service quality, tax socialization, E-Samsat and Sanctions have a simultaneous and partial effect on taxpayer compliance at UPPD Samsat Batulicin, the most dominant variable in this study is satisfaction, it is proven from beta coefficient analysis. Keywords: Knowledge, Awareness, satisfaction, service quality, tax socialization, E-Samsat, Sanctions, Taxpayer Compliance